Digitalization of Bureaucracy and Good Governance: A Literature Review of Indonesian Public Administration Reforms in the Post–New Order Era - Aris Toening Winarni; Dony Bundianto (International Journal of Social Welfare and Family Law, 2024)
This article examines the role of bureaucratic digitalisation in advancing good governance in post-New Order Indonesia based on a narrative literature review. Employing an integrative framework that connects Good Governance theory, E-Government, Digital Era Governance, and Institutional Theory, this study analyses literature published between 1998 and 2024 drawn from academic journals, policy documents, and national–international institutional reports. The findings indicate that, although Indonesia has achieved notable progress in digital regulation and infrastructure, reflected in the adoption of SPBE and the increase in the EGDI from 0.3690 (2012) to 0.6612 (2022), implementation continues to face severe structural and institutional constraints. Five key themes emerge: progressive policy development yet uneven implementation; a transparency paradox between rhetoric and practice; severe interregional digital divides; institutional resistance rooted in patrimonial administrative culture; and the ambivalent effects of digitalisation on public service quality. This study concludes that the digitalisation of bureaucracy has not fundamentally transformed good governance due to an excessive emphasis on technological solutions in the absence of institutional and cultural reconfiguration. Policy recommendations include contextual strategies based on local capacity, sustained investment in civil servant capacity building, and reforms to bureaucratic incentive structures. This study contributes to the e-government literature in developing countries by providing a critical analysis of the persistent gap between policy adoption and actual implementation.